2010
DOI: 10.6090/jarq.44.415
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Six Caffeic Acid Derivatives in Sweetpotato Leaves by High-Performance Liquid Chromatography using a Short Column

Abstract: In 2002, we reported that sweetpotato leaves contained six caffeic acid derivatives, namely, caffeic (4,, and 3,4,5-tri-O-caffeoylquinic (3,4,5-triCQA) acids, which are known to have many physiological functions. A new sweetpotato cultivar 'Suioh' was developed for use of its tops as an edible green by KONARC. It is important to analyze the caffeic acid derivatives efficiently with high-performance liquid chromatography (HPLC) in order to continue developing or selecting new cultivars with higher contents of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…using ChA as the standard substance. Figure 2 shows chromatograms of CA and CQAs measured by high-performance liquid chromatography (HPLC) following the methods of Okuno et al (2010). Briefly, the extract was filtered through a polytetrafluoroethylene membrane (0.20 μm; ADVANTEC, Tokyo, Japan), a 5-μL portion of the filtrate was injected into the HPLC system and it was eluted as described below.…”
Section: Polyphenol Extraction and Quantitative Analysismentioning
confidence: 99%
“…using ChA as the standard substance. Figure 2 shows chromatograms of CA and CQAs measured by high-performance liquid chromatography (HPLC) following the methods of Okuno et al (2010). Briefly, the extract was filtered through a polytetrafluoroethylene membrane (0.20 μm; ADVANTEC, Tokyo, Japan), a 5-μL portion of the filtrate was injected into the HPLC system and it was eluted as described below.…”
Section: Polyphenol Extraction and Quantitative Analysismentioning
confidence: 99%
“…16) In order to quantify CQAs in both sweet potato leaves and storage roots with purple flesh, we modified the conditions because the peaks of anthocyanins in the storage roots of sweet potato with purple flesh were detected to be close to that of CQAs. The modified conditions resulted in good separation between the peaks of CA, CQAs, and anthocyanins.…”
Section: System Selectivitymentioning
confidence: 99%
“…On the other hand, Zheng and Clifford detected 3-CQA and 4-CQA in sweet potato leaves and stems by qualitative analysis using structure-diagnostic LC-MS. 15) Since analytical methods for the quantification of CQAs have not been standardized yet, the analytical values cannot be compared and quality management has not been carried out. CQAs are analyzed by comparing the retention time with that of known standards using HPLC, and the amount of CQAs is calculated as CA or 5-CQA equivalent or compared using the relative amount, 16,17) because CQAs except for 5-CQA cannot be obtained easily as a commercial reagent and they are expensive if available. Therefore, the relative response factor (RRF), which is determined by the analysis of standards and used to compute the true concentrations of compounds in samples, was used for the analysis of CQAs in this study.…”
mentioning
confidence: 99%
“…5) Previous studies have revealed that sweet potato leaves are an excellent source of anti-oxidative compounds, such as caffeic acid (CA) and all known caffeoylquinic acids (CQA). [6][7][8] CQAs are found in plant-derived foods and beverages, and play a crucial role in human health. In recent years, the health benefits of CQAs have attracted particular interest because of their anti-oxidative, anti-inflammatory, anti-microbial, hepatoprotective, anti-cardioprotective, low-density lipoprotein oxidation activities, and neuroprotective effect.…”
mentioning
confidence: 99%
“…79, No. 8,[1308][1309][1310][1311][1312][1313][1314] information is available on their variation as a result of repeated harvesting several times in a year, which is one of the their unique properties. The aim of this work was to examine the effect of repeated harvesting on the content of CA and seven species of CQAs in sweet potato leaves using a single-laboratory validated HPLC method.…”
mentioning
confidence: 99%